2015
DOI: 10.4103/0377-4929.168889
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the trachea

Abstract: Primary salivary gland-type tumors of the lung and airways being unusual, they pose a diagnostic challenge on small biopsies and are usually consigned as non-small cell lung carcinomas. Since the clinical behavior of these tumors is different from the conventional lung tumors, it is important to accurately diagnose them. Among this category of tumors, adenoid cystic carcinoma (ACC) of the lungs and airways is exceedingly rare. Few large studies and maximum case reports have been reported in literature on ACC o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…So far, several large studies and more case reports have been reported in the literature about PACC. This tumor is unrelated to smoking, it appears usually in the fifth decade, and there is no particular sex predilection [ 2 , 4 , 5 ]. Our patient was, so, younger than usually reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, several large studies and more case reports have been reported in the literature about PACC. This tumor is unrelated to smoking, it appears usually in the fifth decade, and there is no particular sex predilection [ 2 , 4 , 5 ]. Our patient was, so, younger than usually reported.…”
Section: Discussionmentioning
confidence: 99%
“…Most ACC show a pattern mixture. Immunostaining is not necessary for the diagnosis but can serve out in several special cases notably in solid or tubular ACCs [ 2 ]. Tumor cells express smooth muscle actin and myosin, the protein S100, and CD117 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary tracheal tumors are overwhelmingly malignant in adult patients and usually benign in children [21][22][23] . Squamous cell carcinoma (SCC) and adenoid cystic carcinoma (ACC) are the 2 most common histologies and represent about two thirds of these tumors in adults [15,21,24,25] . They are followed by other rarer neoplasms such as mucoepidermoid carcinoma, sarcomas, lymphomas, and melanomas [17] .…”
mentioning
confidence: 99%